Pengaruh Rasio Profitabilitas Dan Rasio Leverage Terhadap Peringkat Obligasi (Studi Empiris pada Perusahaan Sub Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2010-2015) - Hanna Mutia Narandika; Fauji Sanusi; Ika Utami Widyaningsih (FEB Universitas Sultan Ageng Tirtayasa, 2016)
This study aims to determine influence profitability that measured by Return on Asset (X1), and leverage that measured by Debt to Equity Ratio (X2) to the Bond Rating (Y) at Banking subsector companies listed in Indonesia Stock Exchange (IDX) period 2010-2015. The population used in this study are the Banking subsector companies listed in Indonesia Stock Exchange (IDX) of the year 2010-2015. The samples were 8 companies from 40 of total population using purpossive sampling method. The analytical method used in this study is logistic regression. The result of this study show that: (1) Profitability has not effect on bond rating, (2) Leverage has not effect on bond rating.